Application of the water pollution rate for assessment of condition of water objects - Белогуров, Виктор Петрович; Бакланова, Виктория Юрьевна (Technology audit and production reserves, 2015)
For integrated assessment of water quality are encouraged to use the water pollution rate (WPR). The WPR allows you generically (one number) to assess the level of water pollution in the range of water-polluting substances from the maximum allowable concentrations to extremely high pollution. The WPR is calculated in accordance with formulas that correspond to a piecewise linear approximation of the logistic curve, reflecting the nature of the changes the status of aquatic ecosystems. Analysis of the theoretical foundation, expert testing and practical application of WPR confirms its suitability for assessing the condition of water objects. The WPR can be used to identify trends and advance detection of potential water protection problems. The WPR is recommended for the harmonization of regulations to address cross-border water protection issues.